The development of soyballs product with addition of gluten and cassava, sweet potato, corn, and potato starch - Mhd Reza Pramudya; Elisa Julianti; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The aim of this research was to evaluate the effect of a meat substitute soy composite flour or okara and gluten with the addition of different starch (cassava starch, sweet potato, corn and potatoes) on the physicochemical characteristics of soyballs. Flour composites were made by mixing soy flour or okara flour and gluten with 6 levels of ratio i.e :K1 = 80%: 20%, K2 = 70%: 30%, K3 = 60%: 40%, K4 = 80%: 20 %, K5 = 70%: 30%, K6 = 60%: 40%, and then proximate analysis and water absorption were analyzed. The results of analysis of composite flour with soy flour and gluten ratio of 80%: 20% and composite flour from okara and gluten flour with a ratio of 60%: 40% had a higher protein content i.e 18,0280% and 9,2110% and a higher water absorption,i.e of 2,8850 g/g and 3,1615 g/g respectively. Both types of comparison were then used as a meat substitute in the manufacture of meatballs with the addition of fillers such as cassava starch, sweet potatoes, corn, and potatoes. The soyballs produces were then analyzed physico-chemically include proximate analysis, color, firmness, water binding power, cooking yield and sensory characteristics.The results showed that differences in the type of flour composites used as meat substitutes and type of filler produces soy meatballs with different quality. In general, soy flour composite and gluten produced of soyballs had a higher protein content than soyballs made from composite flour okara and gluten. The filler that provided good quality soyballs was corn. Corn was good on both soyballs from soy flour and tofu with gluten with the filler of corn had higher protein content and fat content, cooking yield and higher texture values than soyballs from soy flour and tofu with filler of cassava, sweet potato, and potato starch. Keywords : Composite flour, gluten, soybean balls, starch